Peningkatan nilai karakter disiplin peserta didik kelas V sekolah dasar melalui penerapan model value clarification technique - Shinta Ayu Maulana; Hasan Mahfud; Fadhil Purnama Adi (Universitas Sebelas Maret, 2020)
Abstract. The purpose of this research is improving the character value of educational discipline class of the 5th by applying the Value Clarification Technique model. The subject in this research were class of the 5th students at SDN Totosari No. 102 Surakarta in the 2019/2020. The variable in this research includes a variable learning act by applying the Value Clarification Technique model. Data collection using assessment tools consisting of observation sheets, insterviews, and documentation. The technique of data analysis on research uses data triangulasi technique and descriptions. Based on data processing result, the result is 86,67% that shows that the application of the Value Clarification Technique model is successful to enhance the character value of student discipline.